2011
DOI: 10.1093/beheco/arr151
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ecology on sociality in the killer whale (Orcinus orca)

Abstract: Figure 3. Cumulative number of bifurcations across AI levels for the data collected in nearshore Shetland and Eastern Icelandic waters. Significant knots that maximized Z statistics from comparisons of stepwise changes above and below the knot value and which signify social tier delineation were at an AI of 0.84 for Pacific and Scotland mammal-eating killer whales and, although non significant, at 0.86 for the Icelandic data. BECK Andy Foote/NAKID IMAGES RESULTS & DISCUSSION Both Atlantic killer whale groups h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 55 publications
6
62
1
Order By: Relevance
“…In the North Atlantic, the only published study addressing sociality found greater similarities 114 between the Scottish mammal-eating population and Northeast Pacific mammal-eating 115 population relative to residents, despite greater phylogenetic distance, suggesting that ecology 116 drives sociality more than phylogenetic inertia does (Beck et al 2012). The study included a 117 limited dataset from Icelandic herring-eating killer whales and their social structure was not 118 explored in detail.…”
mentioning
confidence: 99%
“…In the North Atlantic, the only published study addressing sociality found greater similarities 114 between the Scottish mammal-eating population and Northeast Pacific mammal-eating 115 population relative to residents, despite greater phylogenetic distance, suggesting that ecology 116 drives sociality more than phylogenetic inertia does (Beck et al 2012). The study included a 117 limited dataset from Icelandic herring-eating killer whales and their social structure was not 118 explored in detail.…”
mentioning
confidence: 99%
“…Four other whales originally seen in Iceland and then photographed in the nearshore waters off Scotland (T-38/12, 997/19, IF-4/21 and 993/62; Beck et al 2012) were re-identified in Iceland. Each of those made at least one intra-annual movement between Iceland and Scotland ( Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…Jakobsson & Stefánsson 1999); thus, specializing on a specific stock may not be an effective strategy. However, this would require the ability to shift between specialized feeding strategies adapted to different prey resources (Similä & Ugarte 1993, Deecke et al 2011, Beck et al 2012. Our understanding of the extent of behavioral plasticity in foraging strategies and to what extent killer whales may switch prey types requires future study, particularly combining seasonal behavioral observations and diet assessment in different feeding contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In the eastern North Atlantic, there is evidence for two partially sympatric populations that may specialize on different prey types . Feeding on either fish or marine mammals is observed in the area, but it is not clear if any groups specialize on specific prey or switch between prey types (Beck et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, behavioral observations suggest that while hunting on seals, North Atlantic killer whales demonstrate behavioral features, such as group size (Beck et al, 2012) and vocal activity (Deecke et al, 2011), which are similar to North Pacific transients, despite being genetically closer to North Pacific residents. The similarity in behavior and vocal activity between the North Pacific transients and North Atlantic killer whales may be due to convergent foraging strategies, but it is not known whether ecological specialization might also lead to convergence in call structure.…”
Section: Introductionmentioning
confidence: 99%